Rancang Bangun Alat Destilasi Bioetanol Berbahan Dasar Nira Aren - Djiofhany Tanaiyo; Evi Sunarti Antu; Syamsu Akuba (Jurnal Teknologi Pertanian Gorontalo (JTPG), 2022)
The palm tree is a type of palm plant that has financial potential and can be used for various purposes. In some areas of Gorontalo, most of the palm sap is used for the manufacture of brown sugar and/or palm sugar. In addition, palm sap can also be used as a basic material for making bioethanol. Bioethanol from palm sap can be used as an alternative fuel to replace fuel oil. Bioethanol obtained from palm sap is generally made through a distillation process or what is known as distillation. The purpose of the research is to design a small-scale bioethanol distillation device so that it is easy to use by sugar palm farmers. The research method applied is divided into two stages, namely design and testing. Bioethanol distillation equipment is made by making components and fabricating. The testing of tools in the process of making bioethanol from palm sap is carried out through several stages, namely pasteurization, fermentation and distillation. The bioethanol distillation apparatus has tubes that are used in the pasteurization, fermentation, and distillation processes. This tube is made of stainless steel with a thickness of 1.5 mm. The pipe and condenser are made of stainless steel with a diameter of 4 inches. The distillation apparatus is equipped with an activated thermometer to measure the temperature that occurs during the heating process of palm sap. Palm sap fermentation was carried out for 3 days at room temperature. The distillation process is carried out at temperatures ranging from 78-80oC. Based on the test results obtained bioethanol with an alcohol content of 55% as much as 200 mL of 5000 mL of basic ingredients. These results indicate that the distillation process is not perfect. Therefore, it is necessary to analyze and improve aspects that can optimize the bioethanol distillation process from palm sap.